Grandfather Tang's story - Tompert, Ann.; Parker, Robert Andrew (New York : Dragonfly Books, 1997)
Grandfather tells a story about shape-changing fox fairies who try to best each other until a hunter brings danger to both of them.
"A tale told with tangrams"--Cover.
Keywords: Storytelling -- Fiction; Foxes -- Fiction; Fairies -- Fiction